Patient Experiences of Decentralized HIV Treatment and Care in Plateau State, North Central Nigeria: A Qualitative Study. (26th February 2017) - Kolawole, Grace O.; Gilbert, Hannah N.; Dadem, Nancin Y.; Genberg, Becky L.; Agaba, Patricia A.; Okonkwo, Prosper; Agbaji, Oche O.; Ware, Norma C.
Abstract : Background. Decentralization of care and treatment for HIV infection in Africa makes services available in local health facilities. Decentralization has been associated with improved retention and comparable or superior treatment outcomes, but patient experiences are not well understood. Methods. We conducted a qualitative study of patient experiences in decentralized HIV care in Plateau State, north central Nigeria. Five decentralized care sites in the Plateau State Decentralization Initiative were purposefully selected. Ninety-three patients and 16 providers at these sites participated in individual interviews and focus groups. Data collection activities were audio-recorded and transcribed. Transcripts were inductively content analyzed to derive descriptive categories representing patient experiences of decentralized care. Results. Patient participants in this study experienced the transition to decentralized care as a series of "trade-offs." Advantages cited included saving time and money on travel to clinic visits, avoiding dangers on the road, and the "family-like atmosphere" found in some decentralized clinics. Disadvantages were loss of access to ancillary services, reduced opportunities for interaction with providers, and increased risk of disclosure. Participants preferred decentralized services overall. Conclusion. Difficulty and cost of travel remain a fundamental barrier to accessing HIV care outside urban centers, suggesting increased availability of community-based services will be enthusiastically received.